(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The incidence of inguinal hernias accounts for about 60% of all types of abdominal hernias. Accordingly, inguinal hernia problems are particularly common in men, and on average, hernioplasties for inguinal hernias make up 40% of all hernia surgeries. In complex and complicated forms of inguinal hernias, finding a proper solution remains challenging. According to the traditional classification, the giant inguinoscrotal hernia is associated with a recurrence rate of 25–35% after hernioplasty. The choice of the surgical method for this type of hernia varies among researchers, depending on the size and shape of the hernia. Currently, there is also no standardized classification based on the size of inguinoscrotal hernias and their recurrence rates.